Ridge subduction sparked reorganization of the Pacific plate‐mantle system 60–50 million years ago. Issue 6 (24th March 2015) - Seton, Maria; Flament, Nicolas; Whittaker, Joanne; Müller, R. Dietmar; Gurnis, Michael; Bower, Dan J.
Abstract A reorganization centered on the Pacific plate occurred ~53–47 million years ago. A "top‐down" plate tectonic mechanism, complete subduction of the Izanagi plate, as opposed to a "bottom‐up" mantle flow mechanism, has been proposed as the main driver. Verification based on marine geophysical observations is impossible as most ocean crust recording this event has been subducted. Using a forward modeling approach, which assimilates surface plate velocities and shallow thermal structure of slabs into mantle flow models, we show that complete Izanagi plate subduction and margin‐wide slab detachment induced a major change in sub‐Pacific mantle flow, from dominantly southward before 60 Ma to north‐northeastward after 50 Ma. Our results agree with onshore geology, mantle tomography, and the inferred motion of the Hawaiian hot spot and are consistent with a plate tectonic process driving the rapid plate‐mantle reorganization in the Pacific hemisphere between 60 and 50 Ma. This reorganization is reflected in tectonic changes in the Pacific and surrounding ocean basins.